Corporate Social Responsibility and Word - of - Mouth Intentions - Kang, Bohyeon; Sivadas, Eugene (Indian Journal of Marketing, 2018)
Companies have invested substantial resources in corporate social responsibility (CSR) initiatives in part to accomplish various strategic objectives. However, firms may utilize CSR to not merely benefit the environment and society, but also to accomplish various firm level strategic objectives and gain competitive advantage. This paper examined the effectiveness of CSR in generating word - of - mouth and integrated the literature in CSR with the literature on WOM and demonstrated the linkages between the two. We tested the model with survey data from consumers in Korea. This was further supplemented with qualitative depth interviews in the United States. The results suggested that CSR image influenced trust and loyalty, and that trust and loyalty had a positive influence on WOM intentions. This research demonstrated that CSR activities could help with generating WOM and should motivate companies to engage in CSR, thus benefiting various stakeholders and society at large.